Polygenic Versus Monogenic Causes of Hypercholesterolemia Ascertained Clinically. Issue 12 (December 2016) - Wang, Jian; Dron, Jacqueline S.; Ban, Matthew R.; Robinson, John F.; McIntyre, Adam D.; Alazzam, Maher; Zhao, Pei Jun; Dilliott, Allison A.; Cao, Henian; Huff, Murray W.; Rhainds, David; Low-Kam, Cécile; et al.
Abstract : Objective—: Next-generation sequencing technology is transforming our understanding of heterozygous familial hypercholesterolemia, including revision of prevalence estimates and attribution of polygenic effects. Here, we examined the contributions of monogenic and polygenic factors in patients with severe hypercholesterolemia referred to a specialty clinic. Approach and Results—: We applied targeted next-generation sequencing with custom annotation, coupled with evaluation of large-scale copy number variation and polygenic scores for raised low-density lipoprotein cholesterol in a cohort of 313 individuals with severe hypercholesterolemia, defined as low-density lipoprotein cholesterol >5.0 mmol/L (>194 mg/dL). We found that (1) monogenic familial hypercholesterolemia–causing mutations detected by targeted next-generation sequencing were present in 47.3% of individuals; (2) the percentage of individuals with monogenic mutations increased to 53.7% when copy number variations were included; (3) the percentage further increased to 67.1% when individuals with extreme polygenic scores were included; and (4) the percentage of individuals with an identified genetic component increased from 57.0% to 92.0% as low-density lipoprotein cholesterol level increased from 5.0 to >8.0 mmol/L (194 to >310 mg/dL). Conclusions—: In a clinically ascertained sample with severe hypercholesterolemia, we found that most patients had a discrete genetic basis detected using a comprehensive screening approach that includes targeted next-generation sequencing, an assay for copy number variations, and polygenic trait scores. Abstract : Supplemental Digital Content is available in the text.